Kemampuan Menulis Teks Persuasi Siswa Kelas VIIIB SMP Negeri 2 Kupang Tahun Pelajaran 2025/2026 - Billy Fernandes Tupa; Sanhedri Boimau; Arnot A. Kolnel (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The purpose of this study is to describe the persuasive text writing ability of eighth-grade students in class VIIIB at SMP Negeri 2 Kupang City in the 2025/2026 academic year. The benefit of this research is to contribute to the development of knowledge in Indonesian language learning, particularly in writing persuasive texts. The method used in this research is a descriptive qualitative method. Data collection techniques were carried out through a persuasive text writing test, which was assessed based on the aspects of persuasive text structure and linguistic aspects. The data obtained were analyzed using descriptive analysis techniques by calculating the average score and the percentage of students who achieved mastery. The results of this study indicate that the level of persuasive text writing ability of students in class VIIIB at SMP Negeri 2 Kupang City is in the